2008
DOI: 10.1159/000148251
|View full text |Cite
|
Sign up to set email alerts
|

Maggots Do Not Survive in Pyoderma Gangrenosum

Abstract: Application of maggots is well established in wound therapy. We report upon 2 patients with leg ulcers due to pyoderma gangrenosum who received immunosuppressive therapy and in whom a reduced survival of maggots (Lucilia sericata sp.) led to ineffectiveness of this therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 39 publications
4
9
0
1
Order By: Relevance
“…Maggots, used to treat other chronic ulcers, have been shown to be ineffective in PG, due to reduced survival in these ulcers. 19 Split-thickness skin grafts and allogeneic-cultured skin equivalents 20 have been employed, usually after induction of remission with immunomodulators. Hyperbaric oxygen therapy is reportedly helpful, even in refractory cases, and may permit reduction of medication doses.…”
Section: Treatmentmentioning
confidence: 99%
“…Maggots, used to treat other chronic ulcers, have been shown to be ineffective in PG, due to reduced survival in these ulcers. 19 Split-thickness skin grafts and allogeneic-cultured skin equivalents 20 have been employed, usually after induction of remission with immunomodulators. Hyperbaric oxygen therapy is reportedly helpful, even in refractory cases, and may permit reduction of medication doses.…”
Section: Treatmentmentioning
confidence: 99%
“…(3) Different metabolic conditions within the wound bed and presence of substances that inhibit larval growth or are toxic to the larvae. The underlying disorder may result in conditions which are not suitable for larval development [23] and/or might affect the nutritional quality of necrotic tissue. It may also be possible that medications taken by some of the patients might have influenced the results.…”
Section: Resultsmentioning
confidence: 99%
“…Actinomycin D, which has antibiotic as well as anti-cancer activity, had a detrimental effect on the larval development of chironomids (non-biting midges) 59 . Maggots used in two patients with pyoderma granolosum leg ulcers showed a reduced survival time, which, it was suggested by the authors, was caused by the use of immunosuppressive drugs (cyclosporine, azathioprine and steroids) in these patients 60 . It is not suggested that the absence of blowfly larvae was the result of antibiotic therapy alone, but the combination of effects caused by radiotherapy, immunosuppression with cytotoxic drugs and the lack of microorganisms as a result of multiple antibiotics, may have played a role.…”
Section: B2 Decompositionmentioning
confidence: 85%